Pengaruh Pola Asuh Permisif terhadap Self-esteem pada Wanita yang Mengalami Kekerasan dalam Berpacaran - Julliant Ghara Kharlinda; Fikrotul Hanifah (IDEA: Jurnal Psikologi, 2026)
This study was conducted to determine how permissive parenting styles can affect self-esteem in women who experience dating violence. Dating violence can occur due to low self-esteem, which can be influenced by, among other things, neglectful parenting styles. Therefore, this study was conducted with the aim of determining the influence of permissive parenting on the self-esteem of victims of dating violence. The research method used was quantitative with purposive sampling on 150 female students. The instruments used were the Permissive Parenting Scale (a=0.834) and the Rosenberg Self-Esteem Scale (a=0.774). The analysis technique used was descriptive and inferential statistics with correlational analysis. The results of this study found a significant influence between permissive parenting and self-esteem (r = 0.341, p<0.01). In conclusion, the higher the level of permissive parenting, the lower the self-esteem.